COLLABORATIVE FILTERING BASED TOP-N RANKED RECOMMENDER SYSTEM: AN IMPLEMENTATION AND COMPARISON METHODOLOGY - Sajid Ansari; Md. Imran; Piyush Kumar Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The trend of digital explorations especially on e-Commerce websites is being witnessed with the fast-growing use of the internet. It led commercials to understand their consumers' behaviour more accordingly. In this paper, we implemented an Artificial Intelligence based technique called Collaborative Filtering on the dataset we created to obtain top-n ranked recommendations for the books on Artificial Intelligence (AI). We also compared our work with other similar implementation of AI based recommender systems to show the differences in the methodologies and approaches that are published by other users.